Evaluation of Public Health Initiatives in Enhancing Polio Vaccination Coverage among Children Under Five in Pakistan: A Cross-Sectional Study - Syed Naveed Haider, Fahad Rehman, Aqib Hanif, Abuzar Ghaffari, Muhammad Zahid Randhawa, Muhammad Hassan Jawad, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Poliomyelitis remains a public health challenge in Pakistan despite ongoing national immunization campaigns. The persistence of wild poliovirus and vaccine-derived outbreaks highlights the need to evaluate the real-world effectiveness of public health interventions in promoting vaccination coverage. Objective: To assess the impact of public health strategies—including door-to-door campaigns, mobile vaccination teams, community health worker outreach, and mass media awareness—on polio vaccination coverage among children under five years of age in Narowal District, Pakistan. Methods: A descriptive cross-sectional study was conducted at DHQ Teaching Hospital Narowal from February 2022 to July 2023. A total of 100 parents or guardians of children aged 0–5 years were interviewed using a structured questionnaire. Data on demographics, vaccination status, and exposure to various public health initiatives were collected. Statistical analysis was performed using SPSS version 25.0, applying chi-square tests and binary logistic regression to assess associations and predictors. Results: Among 100 respondents, 76% reported full vaccination, 17% partial, and 7% no vaccination. Exposure to three or more public health interventions was significantly associated with full vaccination (OR: 3.15; 95% CI: 1.40–7.09; p=0.005). Parental education also showed a positive association (OR: 2.62; p=0.033). Door-to-door campaigns and LHW visits were the most influential strategies. Conclusion: Public health initiatives significantly enhance polio vaccine uptake. Multi-channel interventions involving outreach teams, health workers, and media can improve coverage and help close remaining immunization gaps in Pakistan. Keywords: Poliomyelitis, Vaccination, Coverage, Eradication, Pakistan, Immunization, Outreach, Campaigns, Public health, Compliance